High Blood Uric Acid Is Associated With Reduced Risks of Mild Cognitive Impairment Among Older Adults in China: A 9-Year Prospective Cohort Study - Chen, Chen; Li, Xueqin; Lv, Yuebin; Yin, Zhaoxue; Zhao, Feng; Liu, Yingchun; Li, Chengcheng; Ji, Saisai; Zhou, Jinhui; Wei, Yuan; Cao, Xingqi; Wang, Jiaonan; et al. (Frontiers in Aging Neuroscience, 2021)
Background: It remains unsolved that whether blood uric acid (UA) is a neuroprotective or neurotoxic agent. This study aimed to evaluate the longitudinal association of blood UA with mild cognitive impairment (MCI) among older adults in China. Methods: A total of 3103 older adults (aged 65+ years) free of MCI at baseline were included from the Healthy Aging and Biomarkers Cohort Study (HABCS). Blood UA level was determined by the uricase colorimetry assay and analyzed as both continuous and categorical (by quartile) variables. Global cognition was assessed using the Mini-Mental State Examination four times between 2008 and 2017, with a score below 24 being considered as MCI. Cox proportional hazards models were used to examine the associations. Results: During a 9-year follow-up, 486 (15.7%) participants developed MCI. After adjustment for all covariates, higher UA had a dose-response association with a lower risk of MCI (all P for trend< 0.05). Participants in the highest UA quartile group had a reduced risk (hazard ratio [HR], 0.73; 95% [CI]: 0.55-0.96) of MCI, compared with those in the lowest quartile group. The associations were still robust even when considering death as a competing risk. Subgroup analyses revealed that these associations were statistically significant in younger older adults (65-79 years) and those without hyperuricemia. Similar significant associations were observed when treating UA as a continuous variable. Conclusions: High blood UA level is associated with reduced risks of MCI among Chinese older adults, highlighting the potential of managing UA in daily life for maintaining late-life cognition.